[What lies beneath? Brief history of exploration of volcanic lacustrine beds in the metropolitan area of Rome (central Italy)] - Alessio Argentieri; Giovanni Rotella; Massimo Fabiani; Giuseppe Capelli; Roberto Mazza; Rossana Raffi (Acque Sotterranee, 2024)
[Article in Italian]